Development of an ergonomic risk assessment tool for work postures - Abdol Rahman, Mohd Nasrull (2014)
The most widely used method for assessing work-related musculoskeletal disorders (WMSDs) is still the observational method, mainly because it is inexpensive and practical for use in a wide range of workplaces. However, there are no tools available that cover the wide range of physical risk factors at workplaces. Most of the existing observational methods have not been extensively tested for their reliability and validity during the development process. Therefore, the main objectives of this study are to (1) to develop a new observational technique called the Workplace Ergonomic Risk Assessment (WERA) method and (2) to determine the reliability and validity of the WERA method. The study was conducted in two phases: development of the WERA paper checklist from scientific evidence and literature review (Phase 1) and development of the WERA software program using Visual Basic programming (Phase 2). In the validity trials, the relationship of the main WERA body part scores to the development of pain or discomfort was statistically significant for the wrist, shoulder, and back regions. This shows that the WERA assessment provided a good indication of work related musculoskeletal disorders which may be reported as pains, aches or discomfort in the relevant body area. In the reliability trials, the results of inter-observer reliability demonstrated moderate agreement among the observers (K=0.41) from the feedback survey about the usability of WERA tool. On the other hand, all participants were agreed that the WERA tool was easy and quick to use, applicable to workplace assessment for the wide range of tasks, and valuable at work. The WERA tool has been developed for both paper checklist and software program use. It can be used to identify the physical risk factors associated with WMSDs at workplaces.